Use of library, electronic technologies and resources in the University of the Philippines Diliman Libraries and its effects on users' information needs - Mirasol, John Emanuelle DL (School of Library and Information Studies, University of the Philippines Diliman, 2017)
This study reviews the use of libraries, electronic technologies and resources in the University of the Philippines Diliman Libraries and its effects on users' information needs. The main objective of this study is to determine the users' the electronic resources in the information needs of users, and the factors affecting the use of libraries, electronic technologies and resources in the libraries. The survey was executed in ten (10) selected libraries in University of the Philippines Diliman. The study adopted a stratified random sampling to achieve a sample that approximated the distribution of the library users in different libraries.